Clarifying the in-situ cytotoxic potential of electronic waste plastics - Shi, Pujiang (2021)
Plastics in waste electronics (E-plastics) account for approximately 20% of the entire global electronic waste (E-waste) stream. Most of the E-plastics are not recycled as the presence of toxic additives (e.g. heavy metals, brominated flame retardants (BFRs), antimony, etc.) have associated environmental and health concerns. However, the majority of the studies are focused on quantitative assessment of the toxic constituents in E-plastics, while empirical information regarding the potential toxic effects in humans is largely lacking. To gain a deeper appreciation into the toxicological profile of E-plastics, in situ time-dependent exposures of 6 different human cell lines to a panel of 8 representative E-plastics recovered from liquid crystal displays (LCD), keyboards, screen frames, and wire insulators were conducted. Although several hazardous elements (e.g. Pb, As, Sb, Zn, Cu, etc) were detected at concentrations that far exceed the limit values permitted by the Restriction of Hazardous Substances Directive and EU Directives in the panel E-plastics, in-depth analysis of the 144 unique cell viability data points and live-dead staining experiments suggest that the acute and sub-chronic toxic effects of E-plastics in direct contact with human cells are negligible. These observations agreed with the inductively coupled plasma-optical emission spectrometry data, which revealed that leaching of these toxic additives into the biological milieu is not sufficiently high to trigger a cytotoxic response up to a continuous culture period of 2 weeks. The novel insights gained from this study are posited to further clarify the uncertainty associated with the safety and circular economy implementation of E-plastics.